Asia Pacific Pentecostalism - Austin, Denise A. (Global Pentecostal and Charismatic Studies, 2019)
Asia Pacific Pentecostalism , edited by Denise A. Austin, Jacqueline Grey, and Paul W. Lewis, yields previously untold stories and interdisciplinary analysis of pioneer foundations, denominational growth, leadership training, contextualisation, and community development across East Asia, Southeast Asia, and Oceania. Pentecostalism in the Asia Pacific has made an enormous contribution to its global family-from the more visible influence of Yonggi Cho from Korea to the worship revolutions from Australia (particularly associated with Hillsong) and the lesser known missionary activity from Fiji-each region has contributed significantly to global Christianity. Some communities prospered despite hostile environments and wartime devastation. This volume provides a systematic study of the geographical contexts of Asia Pacific Pentecostalism, including historical development, theological influences, and sociological perspectives. Contributors are: Doreen Alcoran-Benavidez, Dik Allan, Connie Au, Denise A. Austin, Edwardneil Benavidez, John Carter, Michael Chase, Yung Hun Choi, Darin Clements, Shane Clifton, Dynnice Rosanny Engcoy, Michael J. Frost, Luisa J. Gallagher, Sarita D. Gallagher, Kellesi Gore, Adonis Abelard O. Gorospe, Jacqueline Grey, James Hosack, Ken Huff, Paul W. Lewis, Lim Yeu Chuen, Mathew Mathews, Jason Morris, Nyotxay (pseudonym), Saw Tint Sann Oo, Selena Y. Z. Su, Masakazu Suzuki, and Gani Wiyono.